2021
DOI: 10.1111/jon.12936
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve sheath diameter measurement by ultrasound: Evaluation of a standardized protocol

Abstract: Background and Purpose: Treatment of elevated intracranial pressure (ICP) is central to neurocritical care, but not all patients are eligible for invasive ICP-monitoring. A promising noninvasive option is ultrasound measurement of the optic nerve sheath diameter (ONSD). However, meta-analyses of ONSD for elevated ICP show wide confidence intervals. This might be due to baseline variations, inter-rater variability, and varying measurement methods. No standardized protocol has been validated. Corrections for eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 15 publications
2
27
0
4
Order By: Relevance
“…This protocol was further evaluated in a prospective study that demonstrated excellent inter‐ and intrarater reliability for ONSDint and ONSDext assessment. The sample images showed excellent anatomic differentiation with correct marker placement according to author definitions 54 . However, measurements with and without RA Doppler were not performed in this study and it is unclear whether the excellent reliability was due to the protocolized use of RA Doppler or the use of images with good anatomic differentiation and vertical ON orientation.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…This protocol was further evaluated in a prospective study that demonstrated excellent inter‐ and intrarater reliability for ONSDint and ONSDext assessment. The sample images showed excellent anatomic differentiation with correct marker placement according to author definitions 54 . However, measurements with and without RA Doppler were not performed in this study and it is unclear whether the excellent reliability was due to the protocolized use of RA Doppler or the use of images with good anatomic differentiation and vertical ON orientation.…”
Section: Discussionmentioning
confidence: 78%
“…The sample images showed excellent anatomic differentiation with correct marker placement according to author definitions. 54 However, measurements with and without RA Doppler were not performed in this study and it is unclear whether the excellent reliability was due to the protocolized use of RA Doppler or the use of images with good anatomic differentiation and vertical ON orientation. Additionally, lateral gaze can lead to ONSD deformation and smaller ONSD measurements.…”
Section: Other Identified Parametersmentioning
confidence: 91%
“…Topcuoglu et al ( 24 ) suggested to measure both the outermost hypoechogenic space, which they claimed to correspond to the subarachnoid space and the diameter of the hyperechogenic space around the nerve. This way to measure the optic nerve was taken up in other studies ( 25 , 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…ONSD divided by ED increased precision in ICP estimation in two previously published studies 12 , 13 and in one study from our research group, currently undergoing peer review. We therefore used this approach, with a method that has been described in previous publications 14 . In the two previously published studies the optimal cut-off to identify elevated ICP was 0.26 13 and 0.25 12 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore set this as the threshold for elevated ONSD/ED. A recent study from our group showed that ONSD measurements could be performed with excellent inter-rater reliability using a standardized protocol 14 .…”
Section: Introductionmentioning
confidence: 99%